Finite element analysis of deep underground salt caverns - Ćosić Salko; Avdić Mevludin; Sušić Amir; Ljubojev Milenko (Mining and Metallurgy Engineering Bor, 2013)
In this paper, the process of finite element analysis of deep underground salt caverns was described with geometry and material properties related to caverns in the salt mine Tetima-Tuzla, B&H. The 3D model was built based on ultrasound measurement and CAD modelling of planar geometry data. Nonlinear finite element analysis was performed resulting in stresses and deformations data necessary for assessment of cavern stability and time dependent behaviour.